2010
DOI: 10.1007/s00775-010-0740-0
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and growth mechanism of ZnO nanostructures and their cytotoxic effect on human brain tumor U87, cervical cancer HeLa, and normal HEK cells

Abstract: ZnO nanostructures of diverse shape were grown via a solution process with different precursors and conditions. Morphological investigation of the nanostructures was carried out using field emission scanning electron microscopy and transmission microscopy observations and revealed that the nanostructures exhibit a wurtzite phase with an ideal lattice fringe distance of approximately 0.52 nm. The powder crystallinity was examined via X-ray diffraction spectroscopy. Screening results from anticancer studies of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(51 citation statements)
references
References 42 publications
4
44
0
1
Order By: Relevance
“…7 and 8), which is the opposite of what we hypothesized would occur based on the in vitro data. However, the exposure concentrations used in the zebrafish xenograft assay were lower than the effective inhibitory concentrations in in vitro studies, 23,39,40 and we also identified that the ZnO NP agglomerated and underwent considerable dissolution (*47%-50%) when prepared in water (data previously published 28 ). Therefore, we cannot distinguish whether this increase in glioblastoma proliferation is due to a low-exposure NP effect, an ionic effect, or a combination of both.…”
Section: Embryo-larval Zebrafish Xenograft Assay 325supporting
confidence: 59%
See 3 more Smart Citations
“…7 and 8), which is the opposite of what we hypothesized would occur based on the in vitro data. However, the exposure concentrations used in the zebrafish xenograft assay were lower than the effective inhibitory concentrations in in vitro studies, 23,39,40 and we also identified that the ZnO NP agglomerated and underwent considerable dissolution (*47%-50%) when prepared in water (data previously published 28 ). Therefore, we cannot distinguish whether this increase in glioblastoma proliferation is due to a low-exposure NP effect, an ionic effect, or a combination of both.…”
Section: Embryo-larval Zebrafish Xenograft Assay 325supporting
confidence: 59%
“…Our short, 3-day assay allowed us to identify that this ZnO NP is unstable and slightly enhances glioblastoma growth in vivo. These results, in addition to evidence that ZnO NPs seem to only be effective at extremely high concentrations (*62 and 814 mg/L for instance) in in vitro assays, 39,40 suggest that these ZnO NPs in their current state are not a good candidate for future preclinical assessment against glioblastoma in mammalian models. These results illustrate how this short assay successfully combines the rapid economy of in vitro assays with the relevance of slower in vivo rodent assays to aid advances in drug and nanotherapeutic development.…”
Section: Embryo-larval Zebrafish Xenograft Assay 325mentioning
confidence: 97%
See 2 more Smart Citations
“…ZnO NPs were found to be toxic to all human or rodent cells when the concentration was above 15 ppm [145]. ZnO NPs have been studied extensively and they affect different cell types and animal systems [146][147][148][149][150][151]. They are toxic to animals after intra tracheal instillation [152] inhalation [153] and after oral administration [154,150].…”
Section: Safety Concerns With Zno Npsmentioning
confidence: 99%